Interlocking-governed ultra-strong and highly conductive MXene fibers through fluidics-assisted thermal drawing - Zhou, Tianzhu (2024)
High-performance MXene fibers are always of significant interest for flexible textile-based devices. However, achieving high mechanical property and electrical conductivity remains challenging due to the uncontrolled loose microstructures of MXene (Ti3 C2 Tx and Ti3 CNTx ) nanosheets. Herein, high-performance MXene fibers directly obtained through fluidics-assisted thermal drawing are demonstrated. Tablet interlocks are formed at the interface layer between the outer cyclic olefin copolymer and inner MXene nanosheets due to the thermal drawing induced stresses, resulting in thousands of meters long macroscopic compact MXene fibers with ultra-high tensile strength, toughness, and outstanding electrical conductivity. Further, large-scale woven textiles constructed by these fibers offer exceptional electromagnetic interference shielding performance with excellent durability and stability. Such an effective and sustainable approach can be applied to produce functional fibers for applications in both daily life and aerospace.